Evaluating Contract Negotiation Strategy for PT XYZ - Gayashanti, Intan Bayu; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2013)
Oil and Gas operations are the hazardous operation and need huge amount of capital, since then finding efficient resources for this business is critical to eliminate Non Productive Time (NPT) and incident. NPT is near to cost control failure because operation failure means deviation in cost versus budget. The resources needs in this industry should meet the international standard for Oil and Gas. While for high technology services, this is an oligopoly market as already well-known that there is only small amount of Service Company that able to give that such of services that are worldwide class of Service Company while this Company in the research is not listed in Worldwide Oil and Gas Company. To face that situation, Company needs to have high bargaining position and good negotiation strategy to get the best service to support their operation. This research is focusing on finding out the current negotiation strategy in Company and other Company as reference and also doing case study of contract with 1 (one) Worldwide Service Company that has been Company’s partner for a long time. After knowing those, this final project creating initiation material for Company’s negotiation guideline based on Company’s and other Company’s lessons learnt. Next is comparing the current condition with 3-D Negotiation theory to get better strategy in negotiation and higher bargaining position during negotiation with Worldwide Service Company. The results of this final project are recommendations for Company about material of negotiation guideline for Company to get better negotiation strategy and higher bargaining position, supporting tools for negotiators during negotiation preparation process, topic for further study to define the advantages and disadvantages of using existing supplier compare to the new one and enhancing negotiator skill with second and third dimension of 3-D negotiation. Keywords: negotiation, negotiation process, 3-D Negotiation, BATNA, ZOPA, negotiation strategy, negotiation tactics, Oil and Gas Company, negotiation tools, Supply Chain Management